1996
DOI: 10.1016/0014-5793(96)01104-0
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐dependent α‐helix formation promoted by the glycine‐rich octapeptide region of prion protein

Abstract: Prion diseases share a common feature in that the normal cellular prion .protein (PrP c) converts to a proteaseresistant isoform PrP ~c. The c¢-helix-rich C-terminal half of PrP c is partly converted into []-sheet in PrP so. We have examined by Raman spectroscopy the structure of an octapeptide PHGGGWGQ that appears in the N-terminal region of PrP c and a longer peptide containing the octapeptide region. The peptides do not assume any regular structure without divalent metal ions, whereas Cu(II) binding to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
93
1
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(103 citation statements)
references
References 26 publications
8
93
1
1
Order By: Relevance
“…Our results are consistent with earlier reports of copper-induced PrP proteinase resistance (6,7,44) and the delay of disease onset by copper chelation (17). Although copper chelation or an Atp7a mutation can delay the onset of prion disease, it cannot prevent it, even given the 60% reduction in brain copper observed in Atp7a brown mice.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with earlier reports of copper-induced PrP proteinase resistance (6,7,44) and the delay of disease onset by copper chelation (17). Although copper chelation or an Atp7a mutation can delay the onset of prion disease, it cannot prevent it, even given the 60% reduction in brain copper observed in Atp7a brown mice.…”
Section: Discussionsupporting
confidence: 93%
“…Early studies showed that cuprizone, a copper chelating agent, induces neuropathological changes in mice similar to those found in prion diseases (26), suggesting a role for copper in the pathology of prion diseases. More recently, an octapeptide repeat in the N-terminal region of the prion protein has been shown to bind copper (27), and upon binding the protein appears to have a more defined structure in this region, which promotes the conformational shift from an ␣-helical to a ␤-sheet structure (28). There is also evidence from Prnpdeficient mice that their cerebellar cells have an increased sensitivity to the toxicity of copper-containing salts (29), a marked decrease in membrane copper content, and decreased activity of superoxide dismutase 1 (30,31), suggesting that the prion protein may play a role in copper homeostasis in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…34 In addition, short peptides corresponding to the octapeptide repeat motif of PrP have been reported to bind Cu2ϩ. 35,36 Moreover, it has been shown that PrP fragments can be transformed from a predominantly ␣-helical monomeric form to an oligomeric ␤-sheet-rich secondary structure. 37,38 Therefore, PrP sc fragments with a distinct structure could have different neurotoxic properties or a tendency to form aggregates, providing a possible mechanism underlying the differences in phenotypic presentation among GSS variants.…”
Section: Discussionmentioning
confidence: 99%